Speaking to God in Australia: Donald Robinson and the Writing of An Australian Prayer Book (1978) - Shiner, R. J. W. (Studies in church history, 2017)
Archbishop Donald Robinson (b. 1922) had a distinguished career as a New Testament scholar and senior churchman. As a New Testament scholar, he emphasized the linguistic and cultural distance between what Barth called ‘the strange new world of the Bible’ and our own. However, as a senior churchman, Robinson was required to traverse the distance between the Bible and twentieth-century Australians. Through his episcopal leadership, and notably through his work in producing An Australian Prayer Book (1978), Robinson faced the challenge of speaking to Australians about God, and finding the words by which Australians might speak to God. This article will explore the ways in which a prominent scholar and churchman grappled with the linguistic and cultural challenges of speaking about God and to God in contemporary Australia, understood against the background of the crisis of (ir)relevance faced by Australian churches in the decline of the 1960s and 1970s.